2019
DOI: 10.1039/c9dt03759d
|View full text |Cite
|
Sign up to set email alerts
|

Deoxydehydration of polyols catalyzed by a molybdenum dioxo-complex supported by a dianionic ONO pincer ligand

Abstract: Molybdenum cis-dioxo bis-phenolate ONO complexes were synthesized and have been shown to be active for DODH. Catalysts were screened for activity at 190 °C and ambient pressure, and appreciable alkene yields of up to 59% were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…The TON per Mo in these cases is 11 and 6, respectively. [18,20] In our case, the application of the Cp* ligand also gives a quite good alkene product selectivity (55 %) and TON per catalyst (27; i. e. 14 per Mo).…”
Section: Entry Solventmentioning
confidence: 52%
See 3 more Smart Citations
“…The TON per Mo in these cases is 11 and 6, respectively. [18,20] In our case, the application of the Cp* ligand also gives a quite good alkene product selectivity (55 %) and TON per catalyst (27; i. e. 14 per Mo).…”
Section: Entry Solventmentioning
confidence: 52%
“…Very recently, Kilyanek et al reported a dioxomolybdenum complex supported by a dianionic ONO pincer ligand, which catalyzes the DODH of diols using PPh 3 , Na 2 SO 3 , Zn, C, 3-octanol or 2-propanol as reductant. [20] For these ligandsupported "MoO 2 " DODH catalysts similarly low TONs per "MoO 2 " were found as for the AHM systems; the highest TON being around 9.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…5 Metal catalysts that have been successfully explored are rhenium, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] vanadium [24][25][26][27] and molybdenum. [28][29][30][31][32][33][34][35] Rhenium has provided the most efficient and highest yielding catalysts but is the most expensive of the three metals.…”
Section: Introductionmentioning
confidence: 99%